2021
DOI: 10.1155/2021/1725490
|View full text |Cite|
|
Sign up to set email alerts
|

A Coordinated and Optimized Mechanism of Artificial Intelligence for Student Management by College Counselors Based on Big Data

Abstract: The purpose of this article is to perform in-depth research and analysis on the artificial intelligence coordination and optimization mechanism of college counseling student management using big data technology. This study places the collaborative ideological and political work of colleges and universities in the context of big data, and by analyzing its basic connotation and changes in the real situation, it explores the development progression of colleges and universities making full use of big data resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…There were no significant variations in the frequency of postoperative problems and recurrence rates among the three groups in this research, suggesting that all three treatments offer a high assurance of safety. A study [ 23 ] reported the incidence of postoperative pancreatitis in patients with biliary tract stones between 1.8 and 7.2%, and one case of pancreatitis in the ERCP group in this study occurred, which was considered to be due to papilledema obstructing the drainage of pancreatic fluid, or it may be due to excessive amount and speed of contrast injection into the pancreatic duct. A study [ 24 ] found that indwelling ENBD drainage significantly reduced the risk of biliary tract infection and postoperative acute pancreatitis.…”
Section: Discussionmentioning
confidence: 66%
“…There were no significant variations in the frequency of postoperative problems and recurrence rates among the three groups in this research, suggesting that all three treatments offer a high assurance of safety. A study [ 23 ] reported the incidence of postoperative pancreatitis in patients with biliary tract stones between 1.8 and 7.2%, and one case of pancreatitis in the ERCP group in this study occurred, which was considered to be due to papilledema obstructing the drainage of pancreatic fluid, or it may be due to excessive amount and speed of contrast injection into the pancreatic duct. A study [ 24 ] found that indwelling ENBD drainage significantly reduced the risk of biliary tract infection and postoperative acute pancreatitis.…”
Section: Discussionmentioning
confidence: 66%
“…The accuracy and convergence rate of the three classification algorithms varies depending on the size of the number of samples picked in each loop iteration, as shown in the figure. The more examples there are, the more likely the selection engine will choose more useful samples for expert labeling, contributing more to the correct classification model and increasing the classification model's accuracy [ 29 ]. The comparison of classification accuracy and time cost of classification methods is shown in Table 5 .…”
Section: Experimental Simulation and Analysismentioning
confidence: 99%
“…ere are ten different sorts of music genres included in these 1000 files, each having 100 samples. MPCC is utilised to extract the distinctive characteristics of a music signal in this experiment [33,34]. e frame length is 512, and the number of frames is 2133. e sampling frequency is 48000 Hz, the sample bits are 16, the frame length is 512, and the number of frames is 2133 [33,34].…”
Section: Experimental Environment and Data Setmentioning
confidence: 99%
“…MPCC is utilised to extract the distinctive characteristics of a music signal in this experiment [33,34]. e frame length is 512, and the number of frames is 2133. e sampling frequency is 48000 Hz, the sample bits are 16, the frame length is 512, and the number of frames is 2133 [33,34]. In the stage of extracting Mel frequency cepstrum coefficient, 12 dimensional Mel filter is used, and its frequency index is shown in Table 2.…”
Section: Experimental Environment and Data Setmentioning
confidence: 99%